Mutual fund characteristics, risk governance and fund performance in Asean market: a conceptual framework - Shari, Aminah; Mahat, Fauziah (Academic Inspired Networks, 2019)
Investors are able to select superior funds by using fund characteristics in addition. Besides, the chosen fund characteristic act as a benchmark criterion that will affect fund performances and the fundings also vary according categories. The Fund Management Company was issued a letter for lapse with regards to inadequate supervision of risk management activities and due to weakness in operational matters (Securities Commission, 2013). These are also among factors that induce the increasing levels of risk in firms and highlight the importance of an appropriate corporate governance structure for managing risk. The objective of this research is to discuss related literature reviews and follow the construction of conceptual framework that determines fund performance by integrating factors of fund characteristics with firm risk governance. The mediating effect of risk governance on the relationship between fund characteristics and fund performance is also investigated. Data will be analysed by multiple regression analysis via SPSS. This paper recommends further empirical investigation into this line of research to integrate the gap from emerging market evidence related to the fund manager’s efficiency in monitoring skills to meet investment objectives and could be used as an additional criterion by mutual fund investors.